CPARC: Strengthening the Connection between Citizenship and Service-Learning - Martin, Leisa A.; Brown, Amber L. (International Journal of Research on Service-Learning in Teacher Education, 2016)
This study evaluated the impact of scaffolding pre-service teachers service-learning experiences with one semester of a teacher-led service-learning project followed by one semester of a pre-service teacher led service-learning project. Pre and post surveys examined three components of pre-service teacher led service-learning their self-efficacy for service-learning, their civic engagement, and their understanding of how to teach social studies content via a service-learning project. The results indicated statistically significant improvements on all three components. While pre-service teachers made statistically significant improvements on all three areas researched, the results varied regarding individual items used to assess the students. However, the results indicated statistically significant improvements in importance of service-learning to the pre-service teachers and in their intention to implement a service-learning project in the future.